Basic Guide for Organizing a Recreational and Formative Camp - Mejía Calderón, Jorge (2010)
The information in this article is related to a final investigation for a master’s degree. The research had two general objectives. The first was to develop a camp to train 40 youth group leaders. The second objective was to elaborate a guidebook about the organization of a recreational and formative camp. This article presents a guideline, which was grounded through bibliographical revision and experiences obtained at the camp with youth groups. It mentions the importance of this recreational activity as a tool to reinforce the following areas: education, spirituality and physical skills in people. In addition, the guideline includes history about camps and other basic elements of a camp program such as: the foundation, image, philosophy, program structure, leader selection, spirituality, schedule and evaluation.